The use of erythrocyte fragility to assess xenobiotic cytotoxicity - Pagano, Maria; Faggio, Caterina (Cell biochemistry and function, 2015)
The erythrocytes of mammals represent a good model to evaluate the cytotoxicity of molecules, organic and inorganic, natural or synthetic, by cellular damage measure. Indeed, before any investigation on the mechanism of action of different molecules, it is important to perform a cytotoxicity assay. Among the different cytotoxicity assays that assess a possible toxicity in the red blood cells is the rate of haemolysis. This essay is based on the evaluation of the alterations of red cell membranes in the presence of an eventual xenobiotic. Red blood cells are the main cells in circulation, and they are responsible for transporting oxygen; in fact, any alterations of this process could be lethal. The plasma membrane of red blood cells is a multi‐component structure such as to confer to these cells their characteristic biconcave shape, high flexibility, elasticity and deformability. However, there are clear signs of cellular suffering if there are any alterations to this structure. One method of toxicity assessment is based on measurement of the efflux of haemoglobin from suspended red blood cells. Haemolysis, and therefore the loss of haemoglobin, is the signal stability of the cell membrane of the erythrocytes. In recent years, the discovery of programmed cell death in mammalian red blood cells presented a diversification of the response to injury by these a‐nucleated cells. This review shows that mammals' erythrocytes might serve well as a model cell to study on the cellular and molecular mechanisms of many treatments. Copyright © 2015 John Wiley & Sons, Ltd.